3a-66=4a-96

Simple and best practice solution for 3a-66=4a-96 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3a-66=4a-96 equation:



3a-66=4a-96
We move all terms to the left:
3a-66-(4a-96)=0
We get rid of parentheses
3a-4a+96-66=0
We add all the numbers together, and all the variables
-1a+30=0
We move all terms containing a to the left, all other terms to the right
-a=-30
a=-30/-1
a=+30

See similar equations:

| −7=−11+v5 | | 2t-53=t-10 | | -√5x+11=x+3 | | 8-2x^-2=0 | | 2b+6=4b=12 | | 5x-56=6x-70 | | 3w=5w-26 | | 6-0.2x=0 | | 3(2x–5)=4x+7 | | 4p-93=p | | 5/8x=1/8 | | 4x-94=2x-32 | | c+51=10c-30 | | 2v-41=v-22 | | s+5=-3s-35 | | -35=f/7 | | -90=100+c | | 3u-26=u-5 | | u-5=3u-26 | | 5a-17=20+7a | | (5+81)+(2s)=180 | | 28=-4x/7 | | y+4=2y-14 | | 1a+2a=1776 | | 28=4x/8 | | z-30=2z-82 | | 3t-22=t | | 1.06^x=1.4 | | 2x-14=6x-90 | | x-40=2x-100 | | u-8=2u-41 | | 7y-66=y+18 |

Equations solver categories